Osdeni dushi - Radev, Valo (Bulgaria : Sredets at Boyana Film Studio, 1975)
The action takes place during the Spanish Civil War. The accidental meeting of British noblewoman Fanny Horn with Father Eredia, a Jesuit, reverses their destinies. The attraction between them is very strong, yet the priest is devoted to his faith. Influenced by his religious strength, Fanny Horn follows him to a place where a typhus outbreak is raging. Against the background of this inferno, a crime of passion is committed. Fanny fights for Eredia's love but is in the end rejected by his fanatic aescetism. Exhausted by her experiences, Fanny starts taking morphine.
Duration: 02:21:00
Keywords: Fiction films